Organisation‐level and individual‐level predictors of nurse‐reported quality of care in primary care: A multilevel study in China. Issue 4 (19th February 2023) - Wang, Wenhua; Zhang, Jinnan; Nicholas, Stephen; Yang, Huiyun; Maitland, Elizabeth
Abstract: Objectives: Knowledge of the predictors of nursing quality and safety remains a gap in global primary care research. This study examines organisational‐level and nurse‐level predictors of nurse‐reported quality of care from a management perspective. Methods: We recruited 175 primary care nurses in 38 community health centres (CHCs) varying by size and ownership in Jinan, Tianjin, Shenzhen and Shanghai. Guided by the Systems Engineering Initiative for Patient Safety model, the organisation‐level predictors comprised organisational structure, organisational culture, psychological safety and organisational support, while the nurse‐level predictors included organisational commitment and organisational citizenship behaviour. Nurse‐reported quality of care was measured by two questions: "How do you rate the quality of care that you provide?" and "Do you often receive complaints from patients or their family members at work?" Multilevel linear regression models were used to examine the predictors of nurse‐reported quality of care. Results: Among the four organisation‐level predictors, organisational structure, psychological safety and organisational support were positive predictors of nurse‐reported quality of care. Nurses working in CHCs with highly hierarchical organisational structures (Coef. = 0.196, p  = 0.000), a high level of organisational support (Coef. = 0.158, p  = 0.017) and a high level of psychological safety (Coef. = 0.159, p  = 0.035) were more likely to report high quality of care or less likely to receive medical complaints. In terms of nurse‐level predictors, nurses willing to increase their knowledge through continuous education were more likely to report good quality of care (Coef. = 0.107, p  = 0.049) and less likely to receive medical complaints from patients (Coef. = 0.165, p  = 0.041). Conclusions: Potential management levers to improve quality of nursing care include formalised organisational structures, strong organisational support and a psychologically safe environment as well as the provision of training to facilitate continuous education. Implementing these recommendations is likely to enhance the nursing quality in primary care.